Reconocimiento de la personalidad jurídica de los animales : delimitación de la responsabilidad cívil por la mala praxis en procedimientos médico veterinarios - Mora Barrantes, Nazareth 1999- (2024)
This research paper examines the need to recognize legal personality for animals, or alternatively a specific category for them, in order to hold veterinary professionals civilly liable for cases of malpractice based on this recognition. National legislation, case law, and doctrine regarding the treatment of animals in Costa Rica, as well as various forms of liability for improper or negligent actions towards these living beings, were compiled and analyzed, for identifying the protected legal interest. The treatment of animals in the Costa Rican Civil Code was compared with recent reforms in other countries, specifically Argentina and Spain civil codes and regulations governing veterinary practice, aiming to determine the needs for reform in this regulatory framework from a non-anthropocentric perspective.